The role of financial status, attitudes, behaviours and knowledge for overall well-being in Portugal: The mediating role of financial well-being - Junça Silva, A.; Dias, R. (International Journal of Organizational Analysis, 2023)
Purpose Although overall well-being is a well-studied phenomenon, financial well-being only recently has attracted scholars’ attention. Accordingly, this study aimed to understand the relationship between financial well-being, its predictors (financial status, financial behaviour, financial knowledge and financial attitudes) and overall well-being. Design/methodology/approach The authors collected data from 262 working adults. Findings The results showed that only financial status was positively related to financial well-being and the latter was positively related to overall well-being. It was also found that financial well-being mediated the relationship between financial status and overall well-being. In sum, these results showed a multidisciplinary concept of overall well-being and that individuals tend to prioritize financial security over the other components. Research limitations/implications The cross-sectional nature of the data is a limitation. Practical implications Practically speaking, this research is relevant because it highlights the evidence of financial status as an important influence on financial well-being, as well as the role of household income in individuals’ financial satisfaction. Originality/value The study addresses a call for research on the relationship between financial well-being, its main predictors and how these contribute to explain overall well-being.